Management of BKM Da'wah Programs to Enhance Congregational Participation in Regular Islamic Study Sessions - Fania Rahma Yunanda; Ali Akbar (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − This study aims to analyze the management of da'wah programs conducted by the Mosque Prosperity Board (BKM) in enhancing congregational participation in regular Islamic study sessions at Al-Amin Mosque, Medan Perjuangan. Method − This study employed a qualitative approach with a descriptive research design. Data were collected through interviews with the Head of the BKM and several congregation members, supported by observation and documentation. Findings − The findings indicate that the management of the da'wah program, including planning, implementation, and evaluation, has been carried out fairly well. During the planning stage, the BKM prepared the study schedule, determined the topics, and selected speakers according to the needs of the congregation. During the implementation stage, the regular Islamic study sessions were conducted consistently and attracted congregational participation, although participation had not yet reached its optimum level. In the evaluation stage, the BKM assessed the implemented activities as a basis for future improvement. Factors influencing congregational participation included the quality of the study materials, the competence of the speakers, the schedule of the activities, and the available facilities. Overall, effective da'wah program management plays an important role in enhancing congregational participation in regular Islamic study sessions